On the effect of two popular service-level measures on the design of a critical level policy for fast-moving items. (July 2019) - Escalona, P.; Angulo, A.; Weston, J.; Stegmaier, R.; Kauak, I.
Abstract: This paper studies the effect of two service-level measures on the design of a critical-level policy for fast-moving items, where rationing is used to provide differentiated service levels to two classes of demand – high priority and low priority. Using the threshold-clearing mechanism under a strictly increasing non-negative demand to allocate backorders when multiple outstanding orders exist, we formulate service-level problems under type-I, fill-rate, and mixed service-level constraints to determine the optimal parameters of a continuous review ( Q, r ) policy with constant threshold value C to rationing the low-priority class. Based on several monotone properties, we proposed global search algorithms to solve the service-level problems, which guarantee reaching the globally optimal solution for any desired level of accuracy. Further results and a computational study demonstrate how these different models fare against each other in practice.